PENINGKATAN HASIL BELAJARJARING-JARING BANGUN RUANG SEDERHANA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN GEOGEBRA DI KELAS V UPT SDN 19 KOTO TERATAK - Aftana, Aulia; Ningsih, Yarisda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of students at SDN 19 Koto Teratak. This occurred because teachers had not yet used effective learning models and media during the learning process. One model that can be used is the Problem-Based Learning (PBL) model, which encourages students to think critically in solving problems. This can be supported by the use of GeoGebra media, which can be applied in teaching simple three-dimensional net shapes. The purpose of this study is to describe the improvement in students’ learning outcomes using the Problem-Based Learning (PBL) model assisted by GeoGebra on the topic of simple three-dimensional nets in Class V of UPT SDN 19 Koto Teratak. This research is a Classroom Action Research (CAR) that uses both qualitative and quantitative approaches. It was carried out in two cycles, namely Cycle I (two meetings) and Cycle II (one meeting), and consists of four stages: planning, implementation, observation, and reflection. The research instruments used included observation sheets, test sheets, and non-test instruments. The subjects of this study were the teacher and the fifth-grade students of SDN 29 Koto Teratak, totaling 22 students (9 boys and 13 girls). The results of the study show improvements in several areas: the Teaching Module in Cycle I obtained an average of 85.4% (Good), which increased to 95.8% (Very Good) in Cycle II; teacher activity in Cycle I averaged 87.5% (Good), which increased to 96.4% (Very Good) in Cycle II; student activity in Cycle I averaged 83.9% (Good), increasing to 96.4% (Very Good) in Cycle II; and student learning outcomes improved from an average score of 63.4 (Poor) in Cycle I Meeting 1, to 76.1 (Fair) in Cycle I Meeting 2, and further increased to 83.3 (Good) in Cycle II. Based on the results of this research, it can be concluded that learning simple three-dimensional nets using the Problem-Based Learning model assisted by GeoGebra can improve student learning outcomes in Class V of SDN 19 Koto Teratak.